Acute transverse myelitis of the cervical spine secondary to psoas abscess. Issue 1 (December 2016) - He, Hongyu; Jin, Lirong; Ju, Minjie; Tu, Guowei; Luo, Zhe
Abstract Background Acute transverse myelitis is uncommon and presumably results from an autoimmune process or a preceding infection. Most cases of bacterial myelitis are due to hematogenous dissemination from urinary or respiratory tract infections or contiguous spreading from a neighboring infected structure. A psoas abscess rarely spreads to higher levels of the spinal cord. No cases of acute cervical myelitis due to a psoas abscess have been previously reported. Case presentation A 34-year-old man was transferred to our hospital due to progressive muscle weakness, sensory deficits and severe hypotension. Two weeks prior to admission, he had received low back injection to relieve back pain in a healthcare clinic. One day prior to admission, his condition had worsened. On admission, he was tetraplegic with absence of sensation below the level of the suprasternal fossa. A lumbar CT scan demonstrated an abscess in the left psoas, and the magnetic resonance imaging (MRI) scan of the entire spinal suggested a cervical spine infection. A cerebrospinal fluid (CSF) analysis performed before surgery indicated the possibility of bacterial infection. An operation was performed to drain the abscess. Microbiological cultivation revealed a Methicillin-resistant Staphylococcus aureus (MRSA) infection. The patient was administered with vancomycin for 10 days and followed by oral formulations of linezolid for 6 weeks. The patient's general condition improved, and he was successfully discharged. Six months later, a follow-up MRI revealed that the lesion of the cervical spine had been ameliorated, and the sensation and myodynamia of his upper limbs had partially recovered. Conclusion This was a rare case of a high-level cervical spine pyogenic infection complicating psoas abscess. An invasive paravertebral injection procedure was thought to be the initial damaging event that created a port of entry for MRSA into the psoas muscle and caused a subsequent psoas abscess. This case indicated that evaluation of higher levels of the spine is warranted when a psoas abscess coexists with severe weakness.